Meta-analysis indicates better climate adaptation and mitigation performance of hybrid engineering-natural coastal defence measures - Huynh, Lam Thi Mai (2024)
Traditional approaches to coastal defence often struggle to reduce the risks of accelerated climate change. Incorporating nature-based components into coastal defences may enhance adaptation to climate change with added benefits, but we need to compare their performance against conventional hard measures. We conduct a meta-analysis that compares the performances of hard, hybrid, soft and natural measures for coastal defence across different functions of risk reduction, climate change mitigation, and cost-effectiveness. Hybrid and soft measures offer higher risk reduction and climate change mitigation benefits than unvegetated natural systems, while performing on par with natural measures. Soft and hybrid measures are more cost-effective than hard measures, while hybrid measures provide the highest hazard reduction among all measures. All coastal defence measures have a positive economic return over a 20-year period. Mindful of risk context, our results provide strong an evidence-base for integrating and upscaling nature-based components into coastal defences in lower risk areas.